Advanced bronchoscopic techniques for the diagnosis of peripheral pulmonary lesions. Issue 4 (July 2016) - Mudambi, Lakshmi; Ost, David E.
Abstract : Purpose of review: The review describes recent advances in bronchoscopic modalities used to diagnose peripheral pulmonary lesions. Recent findings: The pooled diagnostic yield and sensitivity of radial probe endobronchial ultrasound (r-EBUS) has been reported to be 56% for lesions less than 2 cm and 78% for lesions more than 2 cm and 73%, respectively. The pooled diagnostic yield and sensitivity of electromagnetic navigational bronchoscopy (ENB) has been reported to be 65 and 71%, respectively. However, significant heterogeneity between studies was evident for both r-EBUS and ENB (sensitivity of r-EBUS: I 2  = 75%; sensitivity of ENB: I 2  = 57% and diagnostic yield of ENB: I 2  = 66%). Recent studies show that these technologies do not perform in the clinical setting as well as reported in the literature. Conceptually, the domains of advanced bronchoscopic modalities that affect performance are navigation, maneuverability, and location verification. Combining technologies that deal with different domains, such as ENB (navigation) and r-EBUS (location verification), has led to synergistic effects with improved outcomes. Summary: The performance characteristics of the different advanced bronchoscopic modalities reported in the literature may not be representative of performance in clinical practice because of clinical and statistical heterogeneity in the published literature. However, evidence is accumulating that synergistic combinations of technologies may ultimately lead to better performance.